The four minute mile [videorecording (DVD)] - Goddard, Jim; Huw, Richard; Needles, Nique; Rawlins, Adrian; Philbin, John; Fitz-Gerald, Lewis; Dunbar, Adrian, 1958-; York, Michael, 1942- (BFS Entertainment, 2009)
In 1954, Roger Bannister was the first man to ever run the four minute mile in under four minutes. Together, Roger Bannister, John Landy, Wes Sartec and Denis Johanson stunned and captivated the hearts of the world as they triumphed in battle for the role of the world's fastest runners.